Weighted Integration of Duration Information Across Visual and Auditory Modality Is Influenced by Modality-Specific Attention - Yoshimatsu, Hiroshi; Yotsumoto, Yuko (Frontiers in Human Neuroscience, 2021)
We constantly integrate multiple types of information from different sensory modalities. Generally, such integration is influenced by the modality that we attend to. However, for duration perception, it has been shown that when duration information from visual and auditory modalities is integrated, the perceived duration of the visual stimulus leaned towards the duration of the auditory stimulus, irrespective of which modality was attended. In these studies, auditory dominance was assessed using visual and auditory stimuli with different durations whose timing of onset and offset would affect perception. In the present study, we aimed to investigate the effect of attention on duration integration using visual and auditory stimuli of the same duration. Since the duration of a visual flicker and auditory flutter tends to be perceived as longer than and shorter than its physical duration, respectively, we used the 10 Hz visual flicker and auditory flutter with the same onset and offset timings but different perceived durations. The participants were asked to attend either visual, auditory, or both modalities. Contrary to the attention-independent auditory dominance reported in previous studies, we found that the perceived duration of the simultaneous flicker and flutter presentation depended on which modality the participants attended. To further investigate the process of duration integration of the two modalities, we applied Bayesian hierarchical modeling, which enabled us to define a flexible model in which the multisensory duration is represented by the weighted average of each sensory modality. In addition, to examine whether auditory dominance results from the higher reliability of auditory stimuli, we applied another model to separate the stimulus reliability and attentional effect. These behavioral and modeling results suggest the following: 1) the perceived duration of visual and auditory stimuli is influenced by which modality the participants attended to when we control for the confounding effect of onset–offset timing of stimuli, and 2) the increase of the weight by attention affects the duration integration, even when the effect of stimulus reliability is controlled. Our models can be extended to investigate the neural basis and effects of other sensory modalities in duration integration.